GLOBAL TRENDS IN REPUTATION MANAGEMENT - Daria Kharamurza; Viktoriia Soshynska (Інтегровані комунікації)
The article is devoted to the analysis of global trends in reputation management. The authors studied current world rankings, analyzed reputation studies, and identified the main reputational risks affecting reputation management and forming a company's anti-crisis communication strategy.